Hot forging wire and arc additive manufacturing (HF-WAAM) - Duarte, Valdemar R. (2020)
Fundação para a Ciência e a Tecnologia (FCT -MCTES) for its financial support via the project UID/EMS/00667/2019(UNIDEMI). FCT - MCTES for funding the PhD grantSFRH/BD/139454/2018. TAR acknowledges FCT - MCTES for fundingthe PhD grant SFRH/BD/144202/2019.